Self-incompatibility alleles in important genotypes for apple breeding in Brazil - Brancher,Thyana Lays (2020)
Abstract: The objective of this study was to identify self-incompatibility (S) alleles of advanced breeding selections of apple (Malus × domestica Borkh.). The S-alleles of 42 apple genotypes were analyzed by markers using allele-specific PCR amplification and amplicons digested with restriction endonucleases. Among the screened genotypes were cultivars, advanced selections, and accessions of the Apple Germplasm Bank of Epagri (Caçador, Santa Catarina, Brazil). Two S-alleles were identified in 36 genotypes, and only one S-allele was determined in the other six genotypes. In all, eleven S-alleles were identified among all the genotypes evaluated. The S3 and S5 alleles were most frequent (30.2% and 19.8%, respectively). The identification of S-alleles using molecular markers in important apple tree genotypes is useful for determination of compatible parents for breeding programs.